‘Acumen Metaphoricum’, or seventeenth-century approaches to the theory of concept - Pieczyński, Maciej (Melusine. Old Literature and Culture, 2025)
The article analyses and compares 17th-century theories of conceit developed by Maciej Kazimierz Sarbiewski, Baltasar Gracián, Jacob Masen and Emanuele Tesauro. One of the most significant phenomena in the evolution of theoretical approaches was the growing tendency towards formalism and scholasticism. However, this does not justify the opinion sometimes expressed by researchers that the conceit has lost its cognitive value in favour of purely ornamental character.